Analysis of China's 9-Dash Line Claim in the South China Sea Under International Law - Muhammad Ibrahim Akbar; Prakasa, Satria Unggul Wicaksana (Faculty of Law, Muhammadiyah University of Surabaya, 2023)
The South China Sea area is an area that has a lot of potential. Its very strategic role in various fields such as politics, economics, and security makes it the largest water area with great potential. It contains 266 trillion cubic feet of gas reserves and 7.7 billion barrels of oil reserves. This is the cause of the dispute that occurred in the South China Sea (Luh Gede, et al 2022). There is a clash of diplomacy cultures between ASEAN with the